2010
DOI: 10.1016/j.neuron.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural RNA-Binding Protein Musashi1 Controls Midline Crossing of Precerebellar Neurons through Posttranscriptional Regulation of Robo3/Rig-1 Expression

Abstract: Precisely regulated spatiotemporal gene expression is essential for the establishment of neural circuits. In contrast to the increasing evidence for transcriptional regulation of axon guidance cues and receptors, the role of posttranscriptional regulation in axon guidance, especially in vivo, remains poorly characterized. Here, we demonstrate that the expression of Slit receptor Robo3/Rig-1, which plays crucial roles in axonal midline crossing, is regulated by a neural RNA-binding protein Musashi1 (Msi1). Msi1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 50 publications
(89 reference statements)
5
53
0
Order By: Relevance
“…In contrast, MSI1 has been shown to up-regulate expression of NUMB in gastric tissue (26). MSI1 has also been shown to bind Robo3 mRNA and up-regulate protein production, controlling midline crossing of precerebellar neurons (27). In contrast to many of its other targets, MSI1 is thought to interact with a portion of the Robo3 mRNA coding region that does not contain the MSI1 consensus sequence (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, MSI1 has been shown to up-regulate expression of NUMB in gastric tissue (26). MSI1 has also been shown to bind Robo3 mRNA and up-regulate protein production, controlling midline crossing of precerebellar neurons (27). In contrast to many of its other targets, MSI1 is thought to interact with a portion of the Robo3 mRNA coding region that does not contain the MSI1 consensus sequence (27).…”
mentioning
confidence: 99%
“…MSI1 has also been shown to bind Robo3 mRNA and up-regulate protein production, controlling midline crossing of precerebellar neurons (27). In contrast to many of its other targets, MSI1 is thought to interact with a portion of the Robo3 mRNA coding region that does not contain the MSI1 consensus sequence (27). Other mRNA targets of MSI include doublecortin (28), CDKN1A (29), and c-mos (17).…”
mentioning
confidence: 99%
“…Many miRNAs are specifi cally enriched in neuronal tissues and have been shown to be potent regulators of gene expression during development [reviewed by Klein et al ( 2005 )], thus presaging future discoveries in the translational control of Robos, their ligands and their downstream partners by miRNAs. Apart from miRNAs, post-transcriptional regulation can be achieved by RNA binding proteins such as Musashi1 which was shown to regulate Robo3 expression at the protein level in precerebellar neurons (Kuwako et al 2010 ).…”
Section: Transcriptional and Translational Regulationmentioning
confidence: 99%
“…Msi1 represses the translation of Numb ), a negative regulator of Notch, p21 Cip1 , an inhibitor of cyclin-dependent kinases (Battelli et al, 2006), and doublecortin (Dcx), a microtubule-binding protein involved in neural stem cell migration (Horisawa et al, 2009), but promotes the translation of Robo3, a receptor involved in axonal guidance (Kuwako et al, 2010). Additional targets for Msi1, many of which pertain to the cell cycle, apoptosis, proliferation and differentiation were identified by RIP-chip analysis .…”
Section: The Musashi1 Rna-binding Proteinmentioning
confidence: 99%
“…Additionally, Msi1 is known as a neural stem cell marker useful for studying the migration and biology of neural stem/progenitor cells during development (Kaneko et al, 2000;Chan et al, 2006). In a recent study, Msi1 was shown to be required for neuronal migration of precerebellar neurons via its target gene, Robo3 (Kuwako et al, 2010). Robo3 is a receptor found on astrocytes and is required to receive signals from migrating neurons through the secretion of the Slit1 diffusable protein.…”
Section: Function Of Musashi1 In Normal and Cancer Stem Cellsmentioning
confidence: 99%